Growth and protopectinase production of Geotrichum klebahnii in batch and continuous cultures with synthetic media - Cavalitto, Sebastián Fernando (2000)
ATCC 42397 produces a protopectinase (PPase-SE) with polygalacturonase (PGase) activity. The microorganism was aerobically cultivated in synthetic media. Glucose, fructose and xylose yielded the highest enzyme levels (10–11 PGase units ml−1). Galacturonic acid repressed enzyme production and no growth was obtained with disaccharides and pectin. Specific enzyme activity obtained in an O2-limited culture was similar to that found in nonlimited ones. A growth yield (Y; x/s) of 0.49 g of cell dry weight per gram of glucose consumed was obtained in a typical batch bioreactor culture. Enzyme production was growth associated, and no major products other than biomass and CO2 were detected. The volumetric enzyme activity reached a maximum around D=0.3–0.4 h−1 in glucose-limited continuous cultures. However, it varied strongly (together with microorganism morphology) even after retention times ≥8 at any D tested (0.035–0.44 h−1) though the rest of the culture variables remained fairly constant. No correlation between morphology and enzyme activity could be obtained. Enzyme production was poor in urea- and vitamin-limited continuous cultures. In all cases, biomass and CO2 accounted for ≅100% of carbon recovery though Y; x/s values were different.